Layanan Home Pharmacy Care terhadap Peningkatan Kepatuhan Terapi pada Pasien Diabetes dan Hipertensi: Tinjauan Sistematis Etik dan Regulasi - Widhiartini, Ida Ayu Alit; Ricardo, I Komang Aan Adi; Pebrianti, Ni Putu Wika; Pratama, Putu Yudha Kartika (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2025)
Home pharmacy care is a part of community pharmacy service that is critical in improving                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                         patient adherence, which is a significant challenge in managing chronic diseases. One approach that can help overcome this problem is the practice of home pharmacy care. The current study aimed to evaluate the role of home pharmacy care interventions can enhance medication adherence among diabetic and hypertensive patients and to examine the ethical and regulatory aspects associated with its implementation. A systematic review was conducted based on the PRISMA guidelines, using the keywords “home pharmacy care” AND (diabetes mellitus OR hypertension) AND kepatuhan, home pharmacy care AND diabetes mellitus AND (adherence OR compliance), home pharmacy care AND hypertension AND (adherence OR compliance) on Google Scholar and PubMed databases with a search time limit from January 2015 to May 2025. The ethical and regulatory analysis was conducted by reviewing secondary literature regulating home pharmacy care and professional codes of ethics. Out of a total of 290 identified articles, only 10 met the inclusion criteria for further analysis. Based on the ten reviewed articles, it was stated that home pharmacy care interventions can enhance medication adherence among patients with diabetes mellitus and hypertension. However, the implementation of this service faces challenges, such as ethical concerns and regulatory limitations. The development of comprehensive regulations and consistent application of the code of ethics are expected to strengthen legal protection for pharmacists and improve the quality of home pharmacy care services.